Superfood and Functional Food An Overview of Their Processing and Utilization - Waisundara, Viduranga; Shiomi, Naofumi (IntechOpen, 2017)
This book focuses on the usage and application of plant- and animal-based food products with significant functional properties and health benefits as well as their development into processed food. Many chapters in this book contain overviews on superfood and functional food from South America. Details on the functional properties of apiculture products are also included herein. Additionally, an area that is not widely discussed in academia - pet food with functional properties - is also covered. It is hoped that this book will serve as a source of knowledge and information to make better choices in food consumption and alterations to dietary patterns. It is also recommended for readers to take a look at a related book, Superfood and Functional Food - The Development of Superfoods and Their Roles as Medicine.